2018
DOI: 10.1080/19336934.2018.1549419
|View full text |Cite
|
Sign up to set email alerts
|

Functional interplay between ribosomal protein paralogues in the eRpL22 family in Drosophila melanogaster

Abstract: Duplicated ribosomal protein (RP) genes in the Drosophila melanogaster eRpL22 family encode structurally-divergent and differentially-expressed rRNA-binding RPs. eRpL22 is expressed ubiquitously and eRpL22-like expression is tissue-restricted with highest levels in the adult male germline. We explored paralogue functional equivalence using the GAL4-UAS system for paralogue knockdown or overexpression and a conditional eRpL22-like knockout in a heat-shock flippase/ FRT line. Ubiquitous eRpL22 knockdown with Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 45 publications
1
25
0
Order By: Relevance
“…The function of the RpL22 and RpL22-like paralog pair in Drosophila testis has been explored and it has been suggested that the two proteins are not functionally redundant in development or spermatogenesis. However, knockdown of RpL22 is partially rescued by RpL22-like and vice versa [34, 35]. Further work is needed to directly link effects on ribosome composition and mRNA translational output, as the two paralogs may interact with different pools of mRNA in the testis [35].…”
Section: Discussionmentioning
confidence: 99%
“…The function of the RpL22 and RpL22-like paralog pair in Drosophila testis has been explored and it has been suggested that the two proteins are not functionally redundant in development or spermatogenesis. However, knockdown of RpL22 is partially rescued by RpL22-like and vice versa [34, 35]. Further work is needed to directly link effects on ribosome composition and mRNA translational output, as the two paralogs may interact with different pools of mRNA in the testis [35].…”
Section: Discussionmentioning
confidence: 99%
“…RPL22 paralogs represent an intriguing example of extra ribosomal function-gain and intergenic regulation throughout evolution. Extra ribosomal roles of Rpl22 paralogs were documented in yeast (see below), fruit fly, zebrafish, mice, and humans (Kearse et al, 2011;Mageeney et al, 2018;Zhang et al, 2017;O'Leary et al, 2013;Zhang et al, 2013). Human Rpl22 interacted with human telomerase RNA (Le et al, 2000) and was also sequestered, apparently in competition, by the Epstein-Barr virus (EBV)-encoded RNAs in EBV infected cells, possibly as part of the viral strategy to interfere with translation and growth (Fok, 2006;Houmani et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We used the pair-rule gene, odd-skipped (Odd) to drive tissue-specific expression of an eRpL22-like.IR construct (previously developed by Mageeney et al 16 for expression of inverted repeats (IR) that form short hairpin RNA for eRpL22-like-specific knockdown) for RNAimediated depletion of eRpL22-like within the PE of the eye/antennal imaginal disc. Odd is expressed in margin F I G U R E 6 P-element mediated disruption of eRpL22-like diminishes eRpL22-like staining.…”
Section: In Vivo Erpl22-like Functional Depletion Studies Corroboramentioning
confidence: 99%
“…Whether or not paralogue-specific ribosomes within cells of the developing eye regulate translation of specific mRNAs is unknown, but this proposal should be considered in light of recent findings showing differential association of specific mRNAs on eRpL22-or eRpL22-like ribosomes in the male germline of Drosophila. 16 Thus, even within the ribosomal pool, eRpL22 and eRpL22-like may have distinctive roles in translation regulation. Alternatively, it is interesting to speculate that some eRpL22-like variants (particularly the high molecular mass species identified) may function outside of the ribosomal pathway in specific cells (as our IHC and Western blot data suggest) in apical regions of the PE and in the midpupal IoHC, reserving ribosomal functions for eRpL22 and the 34kD species of eRpL22-like.…”
Section: Unique Patterns Of Erpl22 and Erpl22-like Expression May Smentioning
confidence: 99%
See 1 more Smart Citation